2021
DOI: 10.1097/qad.0000000000002911
|View full text |Cite
|
Sign up to set email alerts
|

Association of epicardial fat with noncalcified coronary plaque volume and with low attenuation plaque in people with HIV

Abstract: a,b,d , for the investigators of the Canadian HIV and Aging Cohort Study Objectives: People with HIV are exposed to a higher risk of coronary artery disease (CAD) compared with the general population. Epicardial fat may play a unique role in promoting coronary atherosclerosis. We measured epicardial fat in participants living with HIV and controls and investigated its association with coronary plaque volume and low attenuation plaque, a marker of plaque vulnerability.Design: This is a cross-sectional study, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Our study results also confirm the previous evidence that EAT volume was affected by HIV infection, and it is associated with duration of HIV [20,22,30]. This confirms the previous study suggesting that PWH had distinct features from HIV-negative individuals in addition to the traditional cardiometabolic risk factors, which are associated with the formation of ectopic fat deposition through multiple mechanisms including persistent inflammation and immune activation [29]. Despite the lack of evidence for the association of ART, such as D4T and ABC in our PWH model, other studies have described that certain ART drugs were associated with increased pericardial fat volume [22].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study results also confirm the previous evidence that EAT volume was affected by HIV infection, and it is associated with duration of HIV [20,22,30]. This confirms the previous study suggesting that PWH had distinct features from HIV-negative individuals in addition to the traditional cardiometabolic risk factors, which are associated with the formation of ectopic fat deposition through multiple mechanisms including persistent inflammation and immune activation [29]. Despite the lack of evidence for the association of ART, such as D4T and ABC in our PWH model, other studies have described that certain ART drugs were associated with increased pericardial fat volume [22].…”
Section: Discussionsupporting
confidence: 92%
“…Coronary calcification remained a significant predictor for EAT volume after adjusting for demographics, HIV status and other cardiometabolic risk factors in our study. Previous reports have also demonstrated the association of epicardial fat and high-risk coronary plaque [14,15,29], possibly resulted from the inflammatory reactions in the local tissues of the arteries. However, we were not able to identify an association of high-risk plaques with EAT volume because of a lack of data on volumetric analysis and information on plaque sub-types.…”
Section: Discussionmentioning
confidence: 94%
“…[16,38,39] We and others have demonstrated that a longer exposure to ART and to some specific ART classes were associated with an increased EF volume. [10,11]…”
Section: Discussionmentioning
confidence: 99%
“…Participant's characteristics stratified by HIV status are listed in Table 1. PLHIV had a similar 10-year Framingham risk score (median of 10% [7][8][9][10][11][12][13][14][15][16] for PLHIV and 9% [7][8][9][10][11][12][13][14][15] for controls, P = .414). PLHIV were more likely to be male (92.0% for PLHIV vs 77.1% for controls, P = .002), to smoke more (median smoking exposure of 6 [0-24.4] pack/years for PLHIV vs 0 [0-8.4] for controls, P = .001) and had a lower cholesterol level (mean total cholesterol of 4.9 ± 1.1 for PLHIV vs 5.3 ± 1.0 for controls, P = .003).…”
Section: Participant's Characteristicsmentioning
confidence: 91%
See 1 more Smart Citation